(3GdeMeOhf ef GdTYQGA hCTYGQges - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi COH CTQa Ndb HGMSf GdBOGH s
(3fSNI eUhQI Yf fSNI HGQjS (B3335s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B325 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B233 s
Keywords: (3GdJGQjNs